2009
DOI: 10.1002/ps.1749
|View full text |Cite
|
Sign up to set email alerts
|

Fitness and maternal effects in hybrids formed between transgenic oilseed rape (Brassica napus L.) and wild brown mustard [B. juncea (L.) Czern et Coss.] in the field

Abstract: These data indicate that there might be enhanced persistence of the transgene in warmer climates. The absence of fitness cost of the transgenes might allow transgenes to persist in ecosystems. These data will contribute to risk assessments of transgene persistence and weed management against the backdrop of global climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Di et al (2009) reported that the F 1 hybrid from wild B. juncea × transgenic canola showed higher fertility than found in our study (Table 1) and reported previously (Bing et al 1996, Frello et al 1995). Di et al (2009) also discussed that vigorous vegetative and reproductive growth of wild B. juncea allowed the maintenance of higher fertility in F 1 hybrid.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Di et al (2009) reported that the F 1 hybrid from wild B. juncea × transgenic canola showed higher fertility than found in our study (Table 1) and reported previously (Bing et al 1996, Frello et al 1995). Di et al (2009) also discussed that vigorous vegetative and reproductive growth of wild B. juncea allowed the maintenance of higher fertility in F 1 hybrid.…”
Section: Discussionsupporting
confidence: 69%
“…Di et al (2009) also discussed that vigorous vegetative and reproductive growth of wild B. juncea allowed the maintenance of higher fertility in F 1 hybrid. Given that wild B. juncea in natural environments is thought to comprise multiple genotypes, a discussion of introgression potential should also take into account this genotypic variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that this potential evolution in flowering time does not depend on the presence of the Bt transgene in the crop, and may even be counter-balanced by positive selection acting on the transgene if the latter was positively associated with maternal genes promoting late flowering and long flowering periods. Recent experiments indeed indicate that the Bt transgene does not induce any fitness costs in hybrids between transgenic B. napus and weedy relatives [37], [38]. It may therefore convey a selective advantage under insect herbivore pressure [39].…”
Section: Discussionmentioning
confidence: 99%